Searching for an integrated self-representation - Istvan Molnar-Szakacs; Shahar Arzy (Communicative & Integrative Biology, 2009)
Recent inquiries into the nature of self-representation have put forward a new and interesting conceptualization of the Self, as a “center of gravity” of one’s private and social behavior. We review recent neuroimaging work that has suggested interactions among brain regions comprising the default state network, including medial and temporo-parietal cortical regions and the mirror neuron system including lateral fronto-parietal regions as two interacting neural systems that work in concert to produce a cohesive self-representation through simulation. Simulation processes—broadly construed here as using existing representations as templates for understanding novel information—are instantiated by these brain systems across a wide range of domains including time, space, physical and social, giving rise to the multi-faceted Self that we all are. Accumulating evidence also suggests, that these simulation processes are used in a multitude of cognitions that constitute the self, including autobiographical memory and prospection, perspective taking, understanding other’s actions and mental states and embodied self-representation.